Prenatal Nutrition and Fetal Macrosomia in Medically Underserved Areas - Inegbenebor, Ute; Ebomoyi, Maureen (Journal of Nutritional Therapeutics, 2012)
Though fetal Macrosomia is often defined as a condition in which the fetus is 4000 grams or more in weight, controversy exists on the exact birth weight that can be used as a bench mark. Fetal macrosomia creates several diagnostic and management difficulties in developed countries. The difficulties experienced by birth attendants in medically underserved areas in developing countries are probably much more. The development of fetal macrosomia is therefore preferably prevented. This article draws attention to observed nutritional habits in Nigeria that are capable of escalating the prevalence of fetal macrosomia in areas that are least equipped to deal the associated complications. Nutritionally dependent prevention strategies that could reduce the incidence of fetal macrosomia in medically underserved areas are suggested.